How to think about time-use data: What inferences can we make about long- and short-run time use from time diaries? - Harley Frazis; Jay Stewart (Institute for the Study of Labor (IZA), 2010)
Time-use researchers are typically interested in the time use of individuals, but time use data are samples of person-days. Given day-to-day variation in how people spend their time, this distinction is analytically important. We examine the conditions necessary to make inferences about the time use of individuals from a sample of person-days. We also discuss whether and how surveys with multiple household members or multiple days are an improvement over single-diary surveys.
Keywords: C81; D13; C83; 330; time use; estimation; survey methods